Effectiveness of clinical healthcare interventions for enhancing the work participation of patients with various health conditions: a synthesis of systematic reviews - Jan L Hoving; Astrid de Wind; Angela G E M de Boer; Annechien Beumer; Faridi S Jamaludin; Lana Kluit; Coen A M van Bennekom (BMJ Open)
Objectives This objectives of this study were to determine the effectiveness of clinical healthcare interventions designed for improving the work participation of patients with various health conditions and identify promising elements within these interventions.Design A systematic literature search was conducted, and a synthesis of systematic reviews (SRs) was performed.Data sources MEDLINE, Embase, Cochrane Library and CINAHL were searched for articles published from January 2012 to December 2023.Eligibility criteria SRs of randomised controlled trials evaluating the effectiveness of interventions that aimed at improving work participation initiated within clinical healthcare in patients being treated for various health conditions were included.Data extraction and synthesis Two authors independently used standardised methods to search and select SRs, and extract data. Our primary outcome was work participation, which could include return-to-work rate or sick leave duration. We were interested in both short-, medium-, as well as long-term outcomes. Risk of bias was assessed using the AMSTAR-2 tool. We used Grading of Recommendations Assessment, Development, and Evaluation (GRADE) to evaluate the certainty of the evidence and findings were summarised in GRADE evidence profiles. We used a deductive synthesis to identify promising intervention elements.Results The health conditions included in the selected SRs were cancer, chronic low back and musculoskeletal pain, coronary heart disease, inflammatory arthritis, complaints of the lumbopelvic region during pregnancy, stroke and traumatic brain injury. Across health conditions, many interventions trended towards small, favourable effects. Moderately certain evidence showed that multidisciplinary and physical interventions enhance work participation at 12 months for people with cancer (risk ratio (RR) 1.23, 95% CI 1.09 to 1.33 and RR 1.23, 95% CI 1.08 to 1.39, respectively), and that multidisciplinary interventions reduce the days of return to work compared with usual care for people with coronary heart disease (40.77 days lower than control, 95% CI −67.19 to −14.35). Low-certainty evidence suggested that multidisciplinary interventions may enhance work participation at 12 months for people with coronary heart disease (RR 1.56, 95% CI 1.23 to 1.98) and reduce the number of sick leave days at 12 months for people with chronic low back pain (82, IQR 51 to 164 vs 175, IQR 91 to 365; p=0.003). Promising elements included (psycho)education, cognitive-behavioural therapy, psychosocial support, group and vocational counselling and physical training.Conclusions There is considerable overlap in clinical healthcare interventions that aim to enhance work participation for patients across health conditions. Although their effects on work participation vary, some conditions show favourable response to multidisciplinary interventions. More evidence is needed on developing tailored interventions and evaluating their cost-effectiveness.PROSPERO registration number CRD42022346552.